Provable Security 4th International Conference, ProvSec 2010, Malacca, Malaysia, October 13-15, 2010, Proceedings - Kurosawa, Kaoru (Security and Cryptology ;, 2010)
This book constitutes the proceedings of the 4th provable security conference held in Malacca, Malaysia in October 2010. The 17 papers presented were carefully reviewed and selected from 47 submissions. The papers are divided in topical sections on identification, auto proofs, signature, hash function, protocol, encryption, and signcryption.